2020
DOI: 10.3390/jcm9093043
|View full text |Cite
|
Sign up to set email alerts
|

Urgent Pericardiocentesis Is More Frequently Needed After Left Circumflex Coronary Artery Perforation

Abstract: Background: Coronary artery perforation (CAP) is a rare but potentially life-threatening complication of percutaneous coronary interventions (PCIs) due to the risk of cardiac tamponade. Strikingly, in contrast to numerous analyses of CAP predictors, only few studies were focused on the predictors of tamponade after PCI, once iatrogenic CAP has occurred. Our aim was to search for clinical and periprocedural characteristics, including the coronary artery involved, associated with the development of acute cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…However, the association of EF with CI-AKI remains controversial. A recent study including 138 patients with acute myocardial infarction found that patients with low EF had a significantly higher rate of CI-AKI after the second step of staged coronary revascularization for acute myocardial infarction 25 . An observational study by Shacham et al showed that worsening EF was an independent predictor of CI-AKI 26 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the association of EF with CI-AKI remains controversial. A recent study including 138 patients with acute myocardial infarction found that patients with low EF had a significantly higher rate of CI-AKI after the second step of staged coronary revascularization for acute myocardial infarction 25 . An observational study by Shacham et al showed that worsening EF was an independent predictor of CI-AKI 26 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous reports addressed the prevalence and the risk profile predisposing to CAPs [2,7]. The combination of multiple factors contributes to the increased risk of CAP and the subsequent adverse events such as pericardial effusion or cardiac tamponade: female sex, older age, calcified coronary arteries, complex coronary lesions, previous coronary artery bypass grafting, or rotational atherectomy procedures [7,[16][17][18]. Studies assessing CAP presented significantly higher morbidity and mortality compared to an uncomplicated PCI, with a potential of an improvement of outcomes post-CS implantation [5,8,19].…”
Section: Discussionmentioning
confidence: 99%